Preparation of future geography teachers for professional activity on a basis competence approach - Hevko, Ihor Vasilievich (Journal of Education, Health and Sport, 2020)
The professional competence of the future teacher of geography, in addition to the level of his own professional education, is determined by his motivated desire for continuous self-education and self-improvement, attitude to work. The axiological component of the studied phenomenon is considered. If we understand professional training as a process of professional development, mastering the experience of future professional activity, we can say that a competent specialist is characterized by value-semantic attitude to future activities. Positive attitude of future teachers to the emergence and development of professional pedagogical competence provides and supports motivational sphere. expressed in need and interest. Preparation of future teachers of geography for professional activity has its own features, which allows to specify and clarify the definition of "preparation of future teachers of geography for professional activity" as an integrated education, including a system of organizational and pedagogical activities focused on educational process - obtaining professional knowledge and skills basics of methods of teaching geography as a pedagogical science and methods of its research, the formation of abilities and qualities necessary for future activities, and I result - the willingness of teachers to the profession. Accordingly, we can formulate a definition of "readiness of future geography teachers for professional activities" as an integral education that is manifested in the needs, desires, motives for professional activities, as well as provides the ability to educational activities based on existing geographical and pedagogical knowledge, skills and emotional experience. value attitude to geographical science.